PERAN GIZI SEIMBANG DALAM PENCEGAHAN STUNTING PADA ANAK 4-6 TAHUN - Rosida Rosida; Rachma Hasibuan (CV. ADIBA AISHA AMIRA, 2025)
The purpose of this study is to identify the role of balanced nutrition in preventing stunting among children aged 4-6 years, focusing on the steps taken by schools to prevent stunting in children aged 4-6 years at TK Al Hikmah Ketapang Banyuwangi. This research uses a qualitative approach with descriptive statistics. The subjects of the study are children aged 4-6 years at TK Al Hikmah Ketapang Banyuwangi. Data collection techniques include observation, interviews, and documentation. Observations were conducted directly by observing the activities of providing supplementary food at TK Al Hikmah Ketapang Banyuwangi. Interviews were conducted with the principal and one parent. Documentation involved collecting photos or other documents that support this research. The data analysis technique used data triangulation, which consists of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the